(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The paper describes the main stages of development of the theory of the text as a separate branch of linguistics, which led to the emergence of many new linguistic trends related to the study of the text, its stylistic devices, characteristics of semantics and structure, methods of operation.